2000
DOI: 10.1203/00006450-200010000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deferoxamine, a Chelator of Free Iron, on Na+,K+-ATPase Activity of Cortical Brain Cell Membrane during Early Reperfusion after Hypoxia-Ischemia in Newborn Lambs

Abstract: Free iron chelation after hypoxia-ischemia can reduce free radical-induced damage to brain cell membranes and preserve electrical brain activity. We investigated whether chelation of free iron with deferoxamine (DFO) preserved cortical cell membrane activity of Na ϩ ,K ϩ -ATPase and electrocortical brain activity (ECBA) of newborn lambs during early reperfusion after severe hypoxia-ischemia. Hypoxia was induced in 16 lambs by decreasing the fraction of inspired oxygen to 0.07 for 30 min, followed by a 5-min pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
0
29
0
2
Order By: Relevance
“…The combination of GMH-IVH with VD diagnosed by neonatal cranial ultrasound is likely to be a useful marker of white matter injury, which may be associated with adverse outcome. Neuroprotective strategies designed to reduce the incidence of haemorrhage or to provide chelation of free iron within the ventricles may lead to an improvement in long-term outcome (Groenendaal et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of GMH-IVH with VD diagnosed by neonatal cranial ultrasound is likely to be a useful marker of white matter injury, which may be associated with adverse outcome. Neuroprotective strategies designed to reduce the incidence of haemorrhage or to provide chelation of free iron within the ventricles may lead to an improvement in long-term outcome (Groenendaal et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, deferoxamine can scavenge superoxide and hydroxyl radicals in concentrations of 0.5-1 mM (28) and prevents neutrophilmediated killing of endothelial cells in cell cultures, which might reduce the inflammatory response after hypoxiaischemia and reperfusion (33). Previous studies in newborn lambs showed that rescue treatment with deferoxamine increased brain perfusion, whereas oxygen metabolism, electrocortical brain activity, and cortical neuronal cell membrane Na ϩ , K ϩ -ATP-ase activity were stable in the first 3.5 h after reperfusion and were comparable to baseline values (7,34). In a clinical study in 50 severely asphyxiated full-term infants, children with severe birth asphyxia and an adverse outcome at 2 y of age had higher levels of NPBI in plasma during the first 8 h of life, which suggests a neurotoxic role of NPBI (35).…”
Section: Peeters-scholte Et Almentioning
confidence: 95%
“…The OL precursors appear deficient in capability of handling the free radicals. The potential explanation for this deficiency is suggested from information derived from studies of experimental models (61,65,66,(75)(76)(77)(78)(79)(80)(81)(82)(83) and limited analyses of autopsied human brain (84 -86). Taken together the findings suggest a delay in the development and the reactivity of antioxidant defenses, especially glutathione peroxidase and catalase (Fig.…”
Section: Maturation-dependent Vulnerability Of Ol Precursorsmentioning
confidence: 99%